Hilda must be dancing - Wilson, Karma (Margaret K. McElderry Books, 2004)
None of her jungle friends can find Hilda Hippo a quieter, less disruptive replacement for dancing, her favorite hobby, until Water Buffalo suggests an activity that allows Hilda to express her dance creativity in a new way.